A tale of three islands: Downstream natural iron fertilization in the Southern Ocean. Issue 5 (22nd May 2016) - Robinson, J.; Popova, E. E.; Srokosz, M. A.; Yool, A.
Abstract: Iron limitation of primary productivity prevails across much of the Southern Ocean but there are exceptions; in particular, the phytoplankton blooms associated with the Kerguelen Plateau, Crozet Islands, and South Georgia. These blooms occur annually, fertilized by iron and nutrient‐rich shelf waters that are transported downstream from the islands. Here we use a high‐resolution (1/12°) ocean general circulation model and Lagrangian particle tracking to investigate whether inter‐annual variability in the potential lateral advection of iron could explain the inter‐annual variability in the spatial extent of the blooms. Comparison with ocean color data, 1998–2007, suggests that iron fertilization via advection can explain the extent of each island's annual bloom, but only the inter‐annual variability of the Crozet bloom. The area that could potentially be fertilized by iron from Kerguelen was much larger than the bloom, suggesting that there is another primary limiting factor, potentially silicate, that controls the inter‐annual variability of bloom spatial extent. For South Georgia, there are differences in the year‐to‐year timing of advection and consequently fertilization, but no clear explanation of the inter‐annual variability observed in the bloom's spatial extent has been identified. The model results suggest that the Kerguelen and Crozet blooms are terminated by nutrient exhaustion, probably iron and or silicate, whereas the deepening of the mixed layer in winter terminates the South Georgia bloom. Therefore, iron fertilization via lateral advection alone can explain the annual variability of the Crozet bloom, but not fully that of the Kerguelen and South Georgia blooms. Key Points: Iron fertilization of blooms downstream of Southern Ocean islands studied with Lagrangian modeling Ocean areas fertilized by simulated iron transport overlap with observed spatial extent of blooms Inter‐annual variability of iron input explains blooms at Crozet but not Kerguelen or South Georgia